A comprehensive narrative review on paradigm shift in the treatment of esophageal and rectal cancer - Chatziisaak, Dimitrios; Burri, Pascal; Steffen, Thomas; Bischofberger, Stephan (Clinical Surgical Oncology, 2025)
The incidence of esophageal and rectal cancer is rising globally. The combination of neoadjuvant chemoradiotherapy (nCRT) with watchful waiting (W&W) strategies has been shown to be an effective approach for maintaining a high quality of life (QoL), particularly in the treatment of rectal cancer. This approach has recently been experimentally extended to the treatment of esophageal cancer. This narrative review provides an overview of the current status of nCRT and watchful waiting (W&W) strategies in both cancer types. The findings of the review indicate that nCRT significantly improves survival and response rates in both cancers. In patients with esophageal cancer, neoadjuvant therapy followed by surgery resulted in a median overall survival that was nearly double the expected survival time and demonstrated high rates of complete pathological response. In the case of rectal cancer, nCRT has been shown to result in high rates of complete response, which in turn has the effect of organ preserving and improving overall oncological outcomes and QoL. The review concludes that the W&W strategies, initially developed for rectal cancer, can be safely extended to selected cases of esophageal cancer, making organ preservation a feasible option that improves patients' quality of life. It is imperative that internationally accepted guidelines and precise patient selection criteria are established to ensure consistent outcomes and enhance long-term monitoring. •Neoadjuvant chemoradiotherapy improves survival in esophageal and rectal cancers.•Watchful waiting strategy enhances quality of life post-neoadjuvant treatment.•Standardization needed for implementing organ-preservation in gastrointestinal cancers.•Careful patient selection is crucial for successful watchful waiting protocols.•Integration of multimodal therapy reduces morbidity and functional impairment.